The Effect Of Plastic Bag On Carbon Adsorbent In Adsorption Of LPG For Gas Storage - Herawan, Safarudin Gazali; Mohamad, Imran Syakir; Mohd Husin, Mohd Haizal; Yusof, Ahmad Anas; Suhaimi, Misha (2005)
Adsorption has been playing an increasingly important role in gas separation and purification. Due to this factor, activated carbons are well developed by chemically treated the adsorbent precursor to produce carbon adsorbent in order to improve adsorption characteristics. This research was conducted with the main purpose to investigate the characteristics of carbon adsorbent from oil palm shell that are mixed with plastic bag to achieve the desired application for LPG gas adsorption to apply in gas storage tank. For investigating the suitability of oil palm shell for preparing into carbon adsorbent, several characteristics has been studied such as physical properties, bulk density and particle size, proximate and ultimate analysis for volatile content and element composition, heating value and burn-off analysis. The batch carbonization and activation processes are carried out in the same reactor with different treatment. All the samples were being tested in Carbon adsorbent Test Bed to determine the LPG gas adsorption and desorption ability. Experimental results showed that the plastic bag affected the carbon adsorbent in adsorbing LPG. This research has shown the great feasibility of using this carbon adsorbent for LPG gas storage, which are applicable and useful in the storage technology such as vehicle fuel storage